2015
DOI: 10.2217/epi.15.2
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Lead Exposure Causes Gender-Specific Changes in the DNA Methylation Profile of DNA Extracted from Dried Blood Spots

Abstract: Aims In this paper, we tested the hypothesis that early life lead (Pb) exposure associated DNA methylation (5mC) changes are dependent on the sex of the child and can serve as biomarkers for Pb exposure. Methods In this pilot study, we measured the 5mC profiles of DNA extracted from dried blood spots (DBS) in a cohort of 43 children (25 males and 18 females; ages from 3 months to 5 years) from Detroit. Result & Discussion We found that the effect of Pb-exposure on the 5-mC profiles can be separated into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 66 publications
9
61
1
Order By: Relevance
“…Additional studies have focused on the sex-specific effects of Pb-induced epigenetic disruptions of the fetus. Using cord blood and blood spots, Sen et al examined differentially methylated regions of the genome that may serve as sex-dependent or independent biomarkers of Pb exposure [61,62]. Interestingly, different patterns were noted when observing CpG methylation in cord blood versus infant blood spots.…”
Section: Leadmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies have focused on the sex-specific effects of Pb-induced epigenetic disruptions of the fetus. Using cord blood and blood spots, Sen et al examined differentially methylated regions of the genome that may serve as sex-dependent or independent biomarkers of Pb exposure [61,62]. Interestingly, different patterns were noted when observing CpG methylation in cord blood versus infant blood spots.…”
Section: Leadmentioning
confidence: 99%
“…However, in blood spots, females showed greater disruption in CpG methylation. Given that males tend to be more susceptible to the effects of Pb exposure, researchers concluded that disruptions in CpG methylation may be adaptive in blood [62]. Notably, Sen et al has also reported that maternal Pb exposure induces epigenetic changes in the germ line of their offspring, impacting DNA methylation in the F2 in humans.…”
Section: Leadmentioning
confidence: 99%
“…Previous studies examining whole blood stored for twelve months at RT in a DNA-protecting solution [17] or placenta tissue stored for two days at RT [33] identified no major DNA methylation changes. Moreover, the feasibility of genome-wide DNA methylation studies using DNA from post-mortem brains [34], as well as archived dried blood spots has also been described before [15,35,36]. To our knowledge this is the first report of a genome-wide interrogation of the DNA methylome in matched whole blood samples stored at RT.…”
Section: Discussionmentioning
confidence: 84%
“…Nevertheless, genetic diversity clearly modifies the body's response to developmental Pb exposure even if the evidence is not detailed [15][16][17][18]. Gender also plays a part, through epigenetics [19]. Children are more at risk from Pb exposure than adults because of their hand to mouth activity, higher respiratory rates and higher gastrointestinal absorption per unit body weight.…”
Section: Causes Of Ill Healthmentioning
confidence: 99%